Assessing developability early in the discovery process for novel biologics - Monica L. Fernández-Quintero; Anne Ljungars; Franz Waibl; Victor Greiff; Jan Terje Andersen; Torleif T. Gjølberg; Timothy P. Jenkins; Bjørn Gunnar Voldborg; Lise Marie Grav; Sandeep Kumar; Guy Georges; Hubert Kettenberger; et al. (mAbs)
Beyond potency, a good developability profile is a key attribute of a biological drug. Selecting and screening for such attributes early in the drug development process can save resources and avoid costly late-stage failures. Here, we review some of the most important developability properties that can be assessed early on for biologics. These include the influence of the source of the biologic, its biophysical and pharmacokinetic properties, and how well it can be expressed recombinantly. We furthermore present in silico, in vitro, and in vivo methods and techniques that can be exploited at different stages of the discovery process to identify molecules with liabilities and thereby facilitate the selection of the most optimal drug leads. Finally, we reflect on the most relevant developability parameters for injectable versus orally delivered biologics and provide an outlook toward what general trends are expected to rise in the development of biologics.